Human abdominal subcutaneous-derived active beige adipocytes carrying FTO rs1421085 obesity-risk alleles exert lower thermogenic capacity - Vámos, Attila; Arianti, Rini; Vinnai, Boglárka Ágnes; Alrifai, Rahaf; Shaw, Abhirup; Póliska, Szilárd; Guba, Andrea; Csősz, Éva; Csomós, István; Mocsár, Gábor; Lányi, Cecilia; Balajthy, Zoltán; et al. (Frontiers in Cell and Developmental Biology, 2023)
White adipocytes store lipids, have a large lipid droplet and few mitochondria. Brown and beige adipocytes, which produce heat, are characterized by high expression of uncoupling protein (UCP) 1, multilocular lipid droplets, and large amounts of mitochondria. The rs1421085 T-to-C single-nucleotide polymorphism (SNP) of the human FTO gene interrupts a conserved motif for ARID5B repressor, resulting in adipocyte type shift from beige to white. We obtained abdominal subcutaneous adipose tissue from donors carrying FTO rs1421085 TT (risk-free) or CC (obesity-risk) genotypes, isolated and differentiated their preadipocytes into beige adipocytes (driven by the PPARγ agonist rosiglitazone for 14 days), and activated them with dibutyryl-cAMP for 4 hours. Then, either the same culture conditions were applied for additional 14 days (active beige adipocytes) or it was replaced by a white differentiation medium (inactive beige adipocytes). White adipocytes were differentiated by their medium for 28 days. RNA-sequencing was performed to investigate the gene expression pattern of adipocytes carrying different FTO alleles and found that active beige adipocytes had higher brown adipocyte content and browning capacity compared to white or inactive beige ones when the cells were obtained from risk-free TT but not from obesity-risk CC genotype carriers. Active beige adipocytes carrying FTO CC had lower thermogenic gene (e.g., UCP1, PM20D1, CIDEA) expression and thermogenesis measured by proton leak respiration as compared to TT carriers. In addition, active beige adipocytes with CC alleles exerted lower expression of ASC1 neutral amino acid transporter (encoded by SLC7A10) and less consumption of Ala, Ser, Cys, and Gly as compared to risk-free carriers. We did not observe any influence of the FTO rs1421085 SNP on white and inactive beige adipocytes highlighting its exclusive and critical effect when adipocytes were activated for thermogenesis.